From ‘Fallen woman’ to ‘New woman’ in victorian novels: Charles Dickens, Thomas Hardy, Charlotte Bronte & Kate Chopin - Monir, Fatimah Binte (BRAC University, 2018)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2017.